The influence of ball in/out of play and possession in elite soccer: Towards a more valid measure of physical intensity during competitive match-play - Jerome, B. W. C.; Stoeckl, M.; Mackriell, B.; Seidl, T.; Dawson, C. W.; Fong, D. T. P.; Folland, J. P. (European Journal of Sport Science, 2023)
The physical demands of soccer match-play have typically been assessed using a low-resolution whole match approach ignoring whether the ball is in or out of play (BIP/BOP) and during these periods which team has possession. This study investigated the effect of fundamental match structure variables (BIP/BOP, in/out of possession) on the physical demands, and especially intensity, of elite match-play. For 1083 matches from a major European league, whole match duration, and player physical tracking data, were divided into BIP/BOP, and in/out of possession periods throughout the match, using on-ball event data. These distinct phases were used to derive absolute (m) and rate (m·min-1) of distance covered in total and within six speed categories during BIP/BOP and in/out possession. The rate of distance covered, an index of physical intensity, was >2-fold greater during BIP vs BOP. Whole match total distance covered was confounded by BIP time and poorly associated with physical intensity during BIP (r = 0.36). Whole match rates of distance covered substantially underestimated those during BIP, particularly for higher running speeds (~-62%). Ball possession markedly effected physical intensity, with the rates of distance covered running (+31%), at high-speed (+30%) and in total (+7%) greater out than in possession. Whole match physical metrics underestimated the physical intensity during BIP, and thus the rate(s) of distance covered during BIP are recommended for accurate measurement of physical intensity in elite soccer. The greater demands of being out of possession support a possession-based tactical approach to minimise fatigue and its negative consequences.